Measuring Organizational Performance: A Case Study of Food Industry SMEs in Surabaya-Indonesia - Sondakh, Oliandes; Lena Ellitan, Budiman Christiananta, (International Journal of Scientific Research and Management (IJSRM), 2017)
The concept of the Balance Scorecard is premised on the need for financial and non-financial indicators that enable a holistic measurement of performance of the organization. The food industry in Indonesia is experiencing positive and significant growth in their performance, however in terms of quality is still not satisfactory. Although performance measurement research has gain great interest, but the effectiveness of the Balance Score Card as a performance measurement tool for food industry SMEs in Surabaya-Indonesia were not widely studied. This research objective was to determine the performance of food industry SMEs in Surabaya-Indonesia by using the Balance Scorecard as a performance measurement tool. This study was designed as a cross-sectional survey of the SMEs food industry in Surabaya-Indonesia. The population was 112 food industry SMEs in Surabaya from which 88 SMEs were used as a sample in this research. Primary data was collected using questionnaires which were administered to managers or owners in the firms. Data was analyzed using descriptive analysis and presented in tables. The study found that on average the respondents agree that they have good organizational performance. Organizational Performance based on Customers Perspective rated as the highest performance, followed by Learning and Growth Perspective; and Internal Business Process Perspective. The Financial Performance Perspective is rated relatively lower.